An Exploratory Application of Eye-Tracking Methods in a Discrete Choice Experiment. (August 2018) - Vass, Caroline; Rigby, Dan; Tate, Kelly; Stewart, Andrew; Payne, Katherine
Background. Discrete choice experiments (DCEs) are increasingly used to elicit preferences for benefit-risk tradeoffs. The primary aim of this study was to explore how eye-tracking methods can be used to understand DCE respondents' decision-making strategies. A secondary aim was to explore if the presentation and communication of risk affected respondents' choices.Method. Two versions of a DCE were designed to understand the preferences of female members of the public for breast screening that varied in how risk attributes were presented. Risk was communicated as either 1) percentages or 2) icon arrays and percentages. Eye-tracking equipment recorded eye movements 1000 times a second. A debriefing survey collected sociodemographics and self-reported attribute nonattendance (ANA) data. A heteroskedastic conditional logit model analyzed DCE data. Eye-tracking data on pupil size, direction of motion, and total visual attention (dwell time) to predefined areas of interest were analyzed using ordinary least squares regressions.Results. Forty women completed the DCE with eye-tracking. There was no statistically significant difference in attention (fixations) to attributes between the risk communication formats. Respondents completing either version of the DCE with the alternatives presented in columns made more horizontal (left-right) saccades than vertical (up-down). Eye-tracking data confirmed self-reported ANA to the risk attributes with a 40% reduction in mean dwell time to the "probability of detecting a cancer" ( P = 0.001) and a 25% reduction to the "risk of unnecessary follow-up" ( P = 0.008).Conclusion. This study is one of the first to show how eye-tracking can be used to understand responses to a health care DCE and highlighted the potential impact of risk communication on respondents' decision-making strategies. The results suggested self-reported ANA to cost attributes may not be reliable.